Bridging Universities and Small Enterprises for Digital Human Resource Management Adoption - Luthfi Imam Fahrudi, Agung Nugroho; Hutahayan, Benny; Hanif Nadanta, Aflah; Ayu Sinta Sekar Jagad, Dyya (Profit: Jurnal Adminsitrasi Bisnis, 2026)
Digital HRM adoption has become increasingly important for higher education institutions and micro, small, and medium enterprises, particularly within the education sector, as organizations seek to improve efficiency, service quality, and decision-making through data-driven HR practices. We conducted a SLR following PRISMA. A Scopus search yielded 472 records; after screening 62 remained, and 17 studies were finally included and thematically analyzed. Findings indicate that best practices in academia comprise integrating HRIS/e-HRM to enable data-driven decisions, deploying AI for recruitment/training/performance assessment, orchestrating learning analytics through institutional maturity models, and strengthening staff capability via structured training; university–SME collaboration accelerates adoption; and the most significant factors for successful implementation in education-sector SMEs. The study contributes an “implementation value chain” that links policy infrastructure competence process analytics AI, reinforced by university–SME collaboration, and offers a practical roadmap for higher-education leaders and education-sector SMEs to prioritize investments, build capabilities, and institutionalize measurable outcomes.